2022
DOI: 10.1038/s41588-022-01082-3
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis defines clonal relationships of ductal carcinoma in situ and recurrent invasive breast cancer

Abstract: Ductal carcinoma in situ (DCIS) is the most common form of preinvasive breast cancer and, despite treatment, a small fraction (5–10%) of DCIS patients develop subsequent invasive disease. A fundamental biologic question is whether the invasive disease arises from tumor cells in the initial DCIS or represents new unrelated disease. To address this question, we performed genomic analyses on the initial DCIS lesion and paired invasive recurrent tumors in 95 patients together with single-cell DNA sequencing in a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…This clearly has potential clinical relevance but requires further validation. Molecular signatures that distinguish poor prognosis DCIS that is likely to progress to invasive carcinoma/metastasise are being investigated, and recent genomic data from the Sloane cohort highlighted clonal similarities between the primary DCIS and the subsequent invasive recurrences in 75% of cases [ 25 ]. Going forward, the molecular profile may provide an attractive companion to standard histopathological examination to dissect the good prognosis microinvasive lesions from those that have the potential to frankly invade/metastasise.…”
Section: Discussionmentioning
confidence: 99%
“…This clearly has potential clinical relevance but requires further validation. Molecular signatures that distinguish poor prognosis DCIS that is likely to progress to invasive carcinoma/metastasise are being investigated, and recent genomic data from the Sloane cohort highlighted clonal similarities between the primary DCIS and the subsequent invasive recurrences in 75% of cases [ 25 ]. Going forward, the molecular profile may provide an attractive companion to standard histopathological examination to dissect the good prognosis microinvasive lesions from those that have the potential to frankly invade/metastasise.…”
Section: Discussionmentioning
confidence: 99%
“…This limitation is systematic in the vast majority of studies of DCIS, as longitudinal sampling cannot be performed. But since not all DCIS patients progress to IDC, there is increasing evidence that host specific factors contribute to DCIS progression or containment 44,45 and cross sectional studies cannot capture their contributions.…”
Section: Discussionmentioning
confidence: 99%
“…Another issue, currently underappreciated, is whether recurrent DCIS has arisen from the primary tumour or is independent. A recent study has shown that ~18% of ‘recurrent’ DCIS may, in fact, be new primary tumours 22 . This proportion of cases will dramatically reduce the power of biomarker studies examining tumour‐intrinsic markers when it is not known which recurrences are truly arising from the primary tumour.…”
Section: Predictive Markers In Dcismentioning
confidence: 99%
“…DCIS can recur both as DCIS in the same breast (ipsilateral) and as invasive cancer, with approximately equal incidence overall. The recurrences are largely molecularly related to the original DCIS, but there is a subset that are clonally unrelated and are considered de‐novo tumours 22 . Because of the histological heterogeneity of DCIS that is also reflected in the immunophenotype, 23 it is a clinical challenge to determine an individual patient's risk of recurrence or progression to invasive disease, thereby making decisions regarding the efficacy of adjuvant therapies difficult.…”
Section: Risk Of Recurrencementioning
confidence: 99%
See 1 more Smart Citation